Call for action to end discrimination against cancer survivors. (September 2018) - Saul, Helen; Liu, Lifang; Meunier, Françoise
Highlights: Increasing number of patients survive cancer in Europe and worldwide. Cancer survivorship research is inefficient, lack of prospective planning. Societal challenges are overlooked. Call for closer collaboration between key stakeholders and stimulate cross-sector communication. Abstract: The growing number of cancer survivors in Europe is a tribute to the success of advances in diagnosis and treatment. But many who have survived the disease go on to face discrimination in the workplace and in their financial affairs. Survivors of cancer may have ongoing physical and psychosocial needs but with appropriate support, many can return to active and fulfilled lives, often including work and travel. Long term collaborative research is needed to monitor the late effects of the disease and its treatment. Psychosocial interventions are effective; demonstrating cost-effectiveness would increase their implementation. This paper calls for a range of actions to directly and indirectly improve the quality of survival after cancer.